STRATEGI GURU PAI DALAM PENERAPAN BUDAYA RELIGIUS SEKOLAH DI SMA NEGERI 3 BATUSANGKAR - Yasmansyah Yasmansyah (al-fikrah: Jurnal Manajemen Pendidikan, 2019)
The purpose of this study was to describe the activities, strategy undertaken as a form of religious culture school in SMANegeri 3 Batusangkar and supporting factors and penghambatn in the application of religious culture school in SMA Negeri 3 Batusangkar. This type of research used in this study is a qualitative research. Sources of data in this study is the Islamic Education teachers and principals and other data sources. Data collection techniques used were interviews, observation and documentation. Data-processing technique that is descriptive qualitative. Analysis of the data used, namely, data reduction, data presentation, drawing conclusions. While the validity of the data by triangulation technique that uses a variety of sources, such as interviews researcher with more than one respondent, observation and documentation. Strategy of teachers of Islamic education in the application of religious culture school that is embedded to the students well.Factors supporting the creation of religious culture school in SMANegeri 3 Batusangkar are internal factors (motivation) originating from within the students, the support of the assembly of teachers SMAN 3 Batusanggkar, their school programs such as FSI (Forum of Islamic Studies), the participation of alumni and the inclusion of some aspects of religious culture into the rules of conduct SMA Negeri 3 Batusangkar. While the inhibiting factor is the limited facilities and infrastructure, some students are still reluctant to implement some aspects of the religious culture of the school, existence of some aspects of the religious culture of the school that can not be required for students to do as well as the limitations of teachers to control students to his home and coupled with still the maximum parental controls to worship the child.